2020
DOI: 10.1088/1757-899x/969/1/012090
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Influence of Dynamic Parameters on the Formation, Structure and Properties of Bimetallic Compounds during Explosion Welding with Simultaneous Stamping

Abstract: This article reports on the study of the influence of dynamic parameters on the formation, structure and properties of bimetallic compounds during explosion welding with simultaneous stamping. The results of the study of the impact of the collision speed and contact speed on the strength, wave parameters and the amount of molten metal obtained by the explosion of a bimetallic compound of the iron + steel 3 alloy are presented. It is shown that the formation of a bimetal during explosion welding is significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…In previous studies, it was shown [10,14] that the kinetic energy of the motion of the welded package can be effectively used for simultaneous stamping, combining this operation with explosion welding. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, it was shown [10,14] that the kinetic energy of the motion of the welded package can be effectively used for simultaneous stamping, combining this operation with explosion welding. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The role of this additional energy is great, since it can be rationally used for simultaneous forming (stamping) of a bimetallic billet. This will eliminate the use of expensive pressing equipment and increase the efficiency of the explosion welding process [12][13][14][15][16][17][18]. To obtain high-quality bimetallic compounds with a given part profile, it is necessary to know the real speed of the package movement and the actual total energy balance of the explosion welding process.…”
Section: Introductionmentioning
confidence: 99%